2003
DOI: 10.1051/0004-6361:20030765
|View full text |Cite
|
Sign up to set email alerts
|

Modeling gas-phase H2O between 5 $\mathsf{\mu}$m and 540 $\mathsf{\mu}$m toward massive protostars

Abstract: Abstract. We present models and observations of gas-phase H 2 O lines between 5 and 540 µm toward deeply embedded massive protostars, involving both pure rotational and ro-vibrational transitions. The data have been obtained for 6 sources with both the Short and Long Wavelength Spectrometers (SWS and LWS) on board the Infrared Space Observatory (ISO) and with the Submillimeter Wave Astronomy Satellite (SWAS). For comparison, CO J = 7−6 spectra have been observed with the MPIfR/SRON 800 GHz heterodyne spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 44 publications
6
64
1
Order By: Relevance
“…Our observed spread in abundances of a factor of ∼100 is much greater than this uncertainty. The same range of abundances is found in other HIFI-based studies of high-mass star-forming regions (van der Tak et al 2010;Chavarría et al 2010), and also in previous work with ISO (Boonman et al 2003) and from the ground (van der Tak et al 2006). …”
Section: Resultssupporting
confidence: 84%
“…Our observed spread in abundances of a factor of ∼100 is much greater than this uncertainty. The same range of abundances is found in other HIFI-based studies of high-mass star-forming regions (van der Tak et al 2010;Chavarría et al 2010), and also in previous work with ISO (Boonman et al 2003) and from the ground (van der Tak et al 2006). …”
Section: Resultssupporting
confidence: 84%
“…2). Boonman et al (2003) observed the outflow in W3 IRS5 in CO J = 7−6 with the JCMT and found a similar line width to what is in the water broad component. We assume that the broad component is due to the outflow.…”
Section: Emission and Absorption Featuresmentioning
confidence: 58%
“…Furthermore, rotational lines have a much higher sensitivity (down to abundances of ∼10 −12 ) than ro-vibrational lines. Clearly, the infrared and (sub-)millimeter techniques are complementary, and both are needed for a complete picture of the chemistry in star-forming regions (e.g., Boonman et al 2003). …”
Section: Observational Techniquesmentioning
confidence: 99%
“…Third, H 2 O remains undetected in several classes of objects, notably low-mass star-forming cores. Finally, the link between the high H 2 O abundances on small scales and the low values on large scales is still poorly understood (e.g., Boonman et al 2003). The HIFI spectrometer and PACS camera onboard the Herschel space observatory will allow key progress on these questions.…”
Section: Oxygen Chemistrymentioning
confidence: 99%